Perumusan Strategi Segmentation, Targeting, dan Positioning untuk Meningkatkan Kinerja Penjualan di Party Store - Kristin Dwi Ermawati; Dwi Hayu Agustini (Publikasi Indonesia, 2025)
This study aims to develop effective marketing strategies using the Segmenting, Targeting, and Positioning (STP) approach to increase sales at Party Store Semarang, which has experienced a continuous decline in revenue over the recent period due to intensified competition. This research employed a quantitative method with a sample of 96 respondents, selected through purposive sampling. Data were collected through questionnaires and analyzed using the clustering method with the help of SPSS to identify market segments. The analysis revealed two main segments: